(untitled) (Journal of Global Accounting, 2023)
The objective of this study was to assess the relationship between Pension Fund Asset Investment and Economic Growth in Nigeria utilizing time series data spanning for a twelve year period, from 2006 to 2017. Secondary data for the period were collected from the National Pension Commission (PenCom) Annual Reports, Central Bank of Nigeria, National Bureau of Statistics and World Bank development indicator (database) of twenty-one licensed pension fund administrator as at 31st December, 2017. The data collected were analyzed and tested for unit root, using the Augmented Dickey-Fuller test using E-Views, 9.0 statistical software. The Ordinary Least Square techniques were used to estimate three models in line with the formulated hypotheses. The results from the models revealed a significant positive relationship between pension fund assets, pension fund contribution, pension fund investment and gross domestic product at 5% level of significance. Consequently, it was recommended inter alia that there should be more emphasis on the management of pension assets in the capital market as well as government bond, real estate and investment trust to boost Gross Domestic Product (GDP) of Nigeria.Keywords: Foreign Directorship, Tobin‟s Q, Board Size, Return on Assets.